2022
DOI: 10.1155/2022/7017610
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanism of Liuwei Dihuang Decoction for Osteoporosis Based on Systematic Biological Strategies

Abstract: Background. Osteoporosis is an important health problem worldwide. Liuwei Dihuang Decoction (LDD) and its main ingredients may have a good clinical effect on osteoporosis. Meanwhile, its mechanism for treating osteoporosis needs to be further revealed in order to provide a basis for future drug development. Methods. A systematic biological methodology was utilized to construct and analyze the LDD-osteoporosis network. After that, the human transcription data of LDD intervention in patients with osteoporosis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Serum ALP is regarded as a diagnostic marker of bone loss in osteoporotic patients and can play an important role in the activation of osteoblasts (50). Empirical evidence in ovariectomized rats has shown that Chinese medicine can significantly increase bone mass and suppress the formation of osteoclasts by inhibiting serum ALP levels (51,52). The result of this meta-analysis also showed that the Jintiange capsule decreased ALP levels.…”
Section: Discussionmentioning
confidence: 60%
“…Serum ALP is regarded as a diagnostic marker of bone loss in osteoporotic patients and can play an important role in the activation of osteoblasts (50). Empirical evidence in ovariectomized rats has shown that Chinese medicine can significantly increase bone mass and suppress the formation of osteoclasts by inhibiting serum ALP levels (51,52). The result of this meta-analysis also showed that the Jintiange capsule decreased ALP levels.…”
Section: Discussionmentioning
confidence: 60%